Pengaruh sistem bagi waris lahan terhadap keberlanjutan usahatani padi guna menunjang ketahanan pangan model Rap-Farm Multidimensional Scaling (MDS) - Amni, Fitriatul; Iskandar, Muhammad Joni; Anwar, M. (Journal of Agribusiness Science and Rural Development, 2025)
The system of agricultural land inheritance plays a significant role in the sustainability of rice farming and local food security. However, this practice often leads to land fragmentation, where agricultural land is divided into increasingly smaller units over time. The land inheritance system affects not only the technical aspects of farming but also has social, economic, and environmental consequences. In the context of Sakra Subdistrict, East Lombok Regency, this inheritance system has implications for the sustainability of rice farming. The objective of this study is to analyze the influence of land inheritance distribution on the sustainability of rice farming as a means to support food security in East Lombok Regency. The research location was purposively selected in Sakra Subdistrict, with a sample consisting of 35 farmers who had already passed down their land to the next generation. Data analysis was conducted using the Rap-Farm approach by applying Multidimensional Scaling (MDS), a modification of the Rapfish (Rapid Assessment Techniques for Fisheries) method. The analysis revealed that the land inheritance mechanism is still carried out within family structures based on deliberation and mutual consensus. The regression results from Rap-Farm show that the economic sustainability dimension had an average score of 36.14, the social dimension 110.71, and the ecological dimension 35.07. These findings suggest that while social aspects remain relatively strong, the economic and ecological dimensions of sustainability require further attention and intervention.